2014
DOI: 10.1039/c4ce01303d
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence visualization of the molecular assembly processes during solvent evaporation via aggregation-induced emission in a cyanostilbene derivative

Abstract: Initial stage of organic crystal formation during solvent evaporation was observed by using aggregation-induced enhanced emission, indicating fluorescence from J-aggregates was established prior to the increase in total intensity at 10 assembly process, which suggested that the kinetics of the transformation of J-aggregates into embryonic nuclei, and subsequently to crystal can be visualized by the fluorescence.Organic molecular materials have wide applications in electroluminescence, solar cells, and pharmace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
(25 reference statements)
2
12
0
Order By: Relevance
“…During the formation of the O-dots, the distance between fluorophores decreases, and this should lead to some autoquenching. Earlier, a similar bathochromic shift in the emission spectra of monomeric fluorophores upon condensation in a polymer matrix was registered by Ito et al for perylene [44], a dibenzoylmethane boron complex [45] and a cyanostilbene derivative [46]. The latter paper also reported that the quantum yield of monomer fluorescence was higher than that of the aggregates.…”
Section: Resultssupporting
confidence: 65%
“…During the formation of the O-dots, the distance between fluorophores decreases, and this should lead to some autoquenching. Earlier, a similar bathochromic shift in the emission spectra of monomeric fluorophores upon condensation in a polymer matrix was registered by Ito et al for perylene [44], a dibenzoylmethane boron complex [45] and a cyanostilbene derivative [46]. The latter paper also reported that the quantum yield of monomer fluorescence was higher than that of the aggregates.…”
Section: Resultssupporting
confidence: 65%
“…In the present system, selective detection of the aggregated state is achieved by making use of the AIE phenomenon. As reported for the CN‐MBE system, temporal changes in the integrated fluorescence intensities are plotted in Figure c. The total fluorescence intensity increased significantly and monotonically after 60 s, and became constant after 180 s. The total fluorescence intensity can be dependent on the amount of HPS aggregates, amorphous and crystals, implying that changes in the fluorescence spectra and fluorescence intensity reflect the formation of aggregates.…”
Section: Figuresupporting
confidence: 53%
“…Interaction with, or binding to, the amyloid fibril results in fluorescence enhancement; thus, ThT is a powerful tool for studying the kinetics of fibril formation. We have reported the aggregation dynamics corresponding to CN‐MBE crystal formation . A sigmoidal function can be used to obtain an estimate of the time required for the aggregation to level off: trueI=Ibase+Itrueprefixmax1+prefixexp[-k(thalf-t)] …”
Section: Figurementioning
confidence: 99%
“…Excitingly, it has been reported that AIE molecules exhibit diverse behaviors in different solvents as a result of the variously restricted molecular motions. Based on these facts, the dynamic visualization of the evaporation process have been studied by using AIE molecules . Firstly, the fluorescent behaviors of AIE molecules in the presence of different water fractions in tetrahydrofuran (THF)/water mixtures have been studied.…”
Section: Process Monitoringmentioning
confidence: 99%
“…Based on these facts, the dynamic visualization of the evaporation process have been studied by using AIE molecules. [63] Firstly,t he fluorescent behaviors of AIE moleculesi nt he presence of different water fractionsi n tetrahydrofuran (THF)/water mixturesh ave been studied. Ac alibration curve was drawn to show the monotonically increasing fluorescent intensity with increasing water fractions in the mixed solvents.…”
Section: Evaporation Dynamicsmentioning
confidence: 99%